Strength and anatomical measures in ACL-injured and Non-injured elite team handball players - Kristianslund, E.; Steffen, K.; Iwasa, J.; Shima, Y.; Myklebust, G.; Bahr, R.; Krosshaug, T. (Arthroscopy: The Journal of Arthroscopic and Related Surgery, 2012)
Non-contact ACL injuries represent a major problem in team sports, especially for females and little is known about risk factors. Therefore, a five-year prospective cohort study has been initiated in the elite division of Norwegian female team handball to identify risk factors for ACL injuries.